Effects of Chromium(III) Ion Doping on Structural, Optical, and Magnetic Properties of Nickel–Cobalt Ferrite Nanoparticle. (8th February 2023) - Senbeto, E. K.; Elangovan, S.
Abstract : Chromium(III)-doped nickel–ferrite nanoparticles, with the general formula Ni0.5 Co0.5 Cr x Fe2− x O4 ( x  = 0.0, 0.10, and 0.20), were prepared by the sol–gel method. The prepared samples were sintered at 700°C for 5 hr. The XRD result showed that the prepared samples are in single-phase partially inverse cubic spinel ferrite structures with space group Fd3m . From the XRD characterization, the average crystallite size for all samples decreased from 39.54 to 30.42 nm and the lattice parameters are found to be 0.8324, 0.8320, and 0.8314 nm for x  = 0.0, 0.10, and 0.20, respectively. The energy dispersive X-ray (EDX) spectroscopy analysis confirmed the presence of all ions as per the stoichiometric ratios. The vibrating sample magnetometer measurements revealed that the saturation magnetization ( M s ), remnant magnetization ( M r ), and coercive fields are found to be decreased with increasing concentration of Cr 3+ ions. The UV–vis spectroscopy analysis showed that the energy bandgap ( E g ) increased with increasing the concentration of Cr 3+ ion from 1.61 to 1.96 eV. The Fourier transform infrared spectra show the two main absorption bands at 407–424 cm −1 and 547–588 cm −1 corresponding to stretching vibrations of metal–oxygen in the octahedral and tetrahedral sites, respectively.